Creation of “Humanized” Mice to Study Human Immunity - Pearson, Todd (2008)
“Humanized” mice are a promising translational model for studying human hematopoiesis and immunity. Their utility has been enhanced by the development of new stocks of immunodeficient hosts, most notably mouse strains such as NOD-scid IL2rγ (null) mice that lack the IL-2 receptor common gamma chain. These stocks of mice lack adaptive immune function, display multiple defects in innate immunity, and support heightened levels of human hematolymphoid engraftment. Humanized mice can support studies in many areas of immunology, including autoimmunity, transplantation, infectious diseases, and cancer. These models are particularly valuable in experimentation where there is no appropriate small animal model of the human disease, as in the case of certain viral infections. This unit details the creation of humanized mice by engraftment of immunodeficient mice with hematopoietic stem cells or peripheral blood mononuclear cells, provides methods for evaluating engraftment, and discusses considerations for choosing the appropriate model system to meet specific goals.